Vibration Vulnerability Identification in Kota Lama Semarang using Microtremor Method - Dwi Purwantoro Sasongko; Gatot Yuliyanto; Zaenal Arifin (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2019)
Kota Lama is one of the landmarks in Semarang Central Java that is located on young alluvial sediment. This area is prone to vibrations stemming from tectonic activities around Semarang. Therefore, measurements were carried out to identify this vibration vulnerability using the microtremor method. These were aimed at obtaining a spatial distribution of vibration vulnerability. There were 29 measurement points each separated by a sampling interval of 50 ms and a duration of 10 minutes.  Ground vibration amplification in this area was found to range from 0.74 to 4.9 with the highest being on the outskirts of Kota Lama. The predominant frequency was found to range from 0.02 to 1.1 Hz. These patterns of high predominant frequency and ground vibration amplification suggest that the central area of Kota Lama needs more attention. High ground shear strain that ranges from 0.02 to 0.86 means that possible event to occur in Kota Lama include landslide, soil compaction, and liquefaction, as is also evident with existing dynamic properties of repeated collapse effect and loading speed effect. Meanwhile, structure of vibration amplification against predominant frequency underneath Kota Lama revealed lateral subsurface discontinuity on its southwest side. It was also found that the contour of ground vibration amplification resembles the shape of Vifjhoek fort.